Which equation is equivalent to —k+0.03+1.01k=-2.45-1.81k?

Answer A on edge Step-by-step explanation:

Answer 6

Equivalent equation 1.82k+2.48 = 0 where Step-by-step explanation: –k+0.03+1.01k = –2.45–1.81k First bring all the values to the left hand side of the equation changing the signs accordingly -k+0.03+1.01k+2.45+1.81k = 0 Bring all the k terms and non k terms together -k+1.01k+1.81k+0.03+2.45 = 0 Solve the k terms and the non k terms 0.01k+1.81k+2.48 = 0 ⇒1.82k+2.48 = 0 Take the non k term to the right hand side which will change the sign 1.82k = -2.48 Rearranging the equation we get Multiply numerator and denominator by 100 k = -1.363

Answer 7

For this case we have the following equation: An equivalent way to write this equation is to multiply both sides of the equation by a scalar.

When multiplying both sides of the equation by 100 we have:

By doing distributive property we have: An equation that is equivalent is:

Hence, the equivalent expression is: –100k + 3 + 101k = –245 – 181k Step-by-step explanation: Equivalent expression is a expression which is similar to the given equation on multiplying by a constant or some constant factor. We have to find the equation which is equivalent to the equation: –k + 0.03 + 1.01k = –2.45 – 1.81k We multiply both side of the equation by 100 to obtain the equivalent expression as: Hence, the equivalent expression is: –100k + 3 + 101k = –245 – 181k

The answer is -100k + 3 + 101k = -245 – 181k. In the equation –k + 0.03 + 1.01k = –2.45 – 1.81k, numbers have two decimals. So, if we multiply both of sides by 100, we will get whole numbers: 100(–k + 0.03 + 1.01k) = 100(–2.45 – 1.81k). 100 * (-k) + 100 * 0.03 + 100 * 1.01k = 100 * (-2.45) + 100 * (-1.81k). -100k + 3 + 101k = -245 – 181k.

- How to Get Bad Credit Online Loans for Fast Emergency Funding - February 1, 2023
- What does an audio engineer do in post-production? - February 1, 2023
- Men and Women of the Civil War Crossword? - February 1, 2023